Epoxy–amine oligomers from terpenes with applications in synergistic antifungal treatments. Issue 34 (1st August 2019) - O'Brien, Dara M.; Vallieres, Cindy; Alexander, Cameron; Howdle, Steven M.; Stockman, Robert A.; Avery, Simon V.
Abstract : Epoxy–amine oligomers synthesised from a renewable terpenoid feedstock are found to act in synergy with known antifungal drug amphotericin B against Candida albicans, and fungicide IPBC against Trichoderma virens . Abstract : A bis-epoxide monomer was synthesised in two steps from ( R )-carvone, a terpenoid renewable feedstock derived from spearmint oil, and used to prepare β-aminoalcohol oligomers in polyaddition reactions with bis-amines without requiring solvent or catalyst. A sub-set of the resultant materials were readily water soluble and were investigated for antifungal activity in combination with the fungicide iodopropynyl-butylcarbamate (IPBC) or the antifungal drug amphotericin B. The oligo-(β-aminoalcohol)s alone were inactive against Trichoderma virens and Candida albicans but in combination with IPBC and amphotericin B demonstrated synergistic growth-inhibition of both fungi. Quantitative analysis showed that the presence of the terpene-based oligomers decreased the minimum inhibitory concentration (MIC) of IPBC by up to 64-fold and of amphotericin B by 8-fold. The efficacy of the combined formulation was further demonstrated with agar disk diffusion assays, which revealed that IPBC and amphotericin B reduced the growth of the fungi, as shown by zones of inhibition, to a greater extent when in the presence of the oligo-(β-aminoalcohol)s. These data suggest potential future use of these renewable feedstock derived oligomers in antifungal material and related biomedical applications.